Leaders' Efforts to Improve Teacher Performance through the Implementation of Total Quality Management in Modern Islamic Boarding Schools - Al Imam, Tubagus Bay Achmad (Universitas Pakuan, 2023)
This study aims to analyze the efforts of school leaders in improving teacher performance through the implementation of Total Quality Management (TQM) principles in modern Islamic boarding schools (Pondok Pesantren Modern). Using a qualitative descriptive approach, the research explores leadership practices that integrate continuous improvement, participatory decision-making, and quality assurance systems within educational management. Data were collected through interviews, observations, and documentation involving school principals, teachers, and administrative staff in a modern Islamic boarding school setting. The findings reveal that leaders play a pivotal role as change agents in establishing a culture of quality by promoting teamwork, accountability, and innovation in teaching practices. Through consistent monitoring, feedback mechanisms, and the application of TQM’s Plan-Do-Check-Act (PDCA) cycle, teacher performance significantly improved, particularly in instructional planning, classroom management, and student learning outcomes. Moreover, the integration of TQM fosters shared responsibility and alignment between organizational goals and individual teacher competencies. The study concludes that leadership based on TQM principles contributes not only to teacher professionalism but also to the sustainability of educational excellence in faith-based institutions that combine traditional values with modern management practices.